Calculation of the Target Lumbar Lordosis Angle for Restoring an Optimal Pelvic Tilt in Elderly Patients With Adult Spinal Deformity. Issue 4 (February 2016) - Yamato, Yu; Hasegawa, Tomohiko; Kobayashi, Sho; Yasuda, Tatsuya; Togawa, Daisuke; Arima, Hideyuki; Oe, Shin; Iida, Takahiro; Matsumura, Akira; Hosogane, Naobumi; Matsumoto, Morio; Matsuyama, Yukihiro
Abstract : Study Design: This investigation consisted of a cross-sectional study and a retrospective multicenter case series. Objective: This investigation sought to identify the ideal lumbar lordosis (LL) angle for restoring an optimal pelvic tilt (PT) in patients with adult spinal deformity (ASD). Summary of Background Data: To achieve successful corrective fusion in ASD patients with sagittal imbalance, it is essential to correct the sagittal spinal alignment and obtain a suitable pelvic inclination. We determined the LL angle that would restore the optimal PT following ASD surgery. Methods: The cross-sectional study included 184 elderly volunteers (mean age 64 years) with an Oswestry Disability Index score less than 20%. The relationship between PT or LL and the pelvic incidence (PI) in normal individuals was investigated. The second study included 116 ASD patients (mean age 66 years) who underwent thoracolumbar corrective fusion at 1 of 4 spine centers. The postoperative PT values were calculated using the parameters measured. On the basis of these studies, an ideal LL angle was determined. Results: In the cross-sectional study, the linear regression equation for the optimal PT as a function of PI was "optimal PT = 0.47 × PI – 7.5." In the second study, the postoperative PT was determined as a function of PI and corrected LL, using the equation "postoperative PT = 0.7 × PI – 0.5 × corrected LL + 8.1." The target LL angle was determined by mathematically equalizing the PTs of these 2 equations: "target LL = 0.45 × PI + 31.8." Conclusion: The ideal LL angle can be determined using the equation "LL = 0.45 × PI + 31.8, " which can be used as a reference during surgical planning in ASD cases. Level of Evidence: 4